Effects of clinical Pilates exercises on cardiovascular endurance and psychosomatic parameters on primary caregivers of special needs children: A randomized controlled trial - Senturk, Yazgi; Kirmizigil, Berkiye; Tuzun, Emine Handan (Ios Press, 2021)
OBJECTIVE: Our objective was to investigate the effects of clinical Pilates exercises (CPE), applied to the primary caregivers of special needs children, on cardiovascular endurance (CVE) and psychosomatic parameters in comparison to a control group. METHODS: Fifty-five primary caregivers of special needs children, divided into two groups as the CPE and control groups, were included in the study. The six-minute walk test, the Fatigue Severity Scale, the Coping Orientation for Problems Experienced (COPE) Inventory, the Beck Depression Inventory and the State-Trait Anxiety Inventory were used to measure CVE, fatigue severity, attitudes toward coping with problems, depression levels and anxiety levels, respectively. RESULTS: Statistically significant differences between the groups in favor of the CPE group were found concerning the denial parameter of COPE, fatigue (which was the primary outcome), depression and anxiety (all p values < 0.05). Statistically significant intragroup comparison differences were only detected in the CPE group in the fatigue, depression, anxiety and COPE (use of instrumental and emotional social support and focus on and venting of emotions) questionnaire results (all p values < 0.05). CONCLUSIONS: CPE are an applicable and effective method for the primary caregivers of special needs children in improving psychosomatic parameters, albeit not effective for CVE. It is recommended to investigate the long-term effects of clinical Pilates exercises on a similar group.
Keywords: Special needs child; primary caregiver; psychosomatic questionnaire; clinical pilates; exercise